Immuno-oncology-101: overview of major concepts and translational perspectives. (October 2018) - Allard, B.; Aspeslagh, S.; Garaud, S.; Dupont, F.A.; Solinas, C.; Kok, M.; Routy, B.; Sotiriou, C.; Stagg, J.; Buisseret, L.
Abstract: Cancer immunotherapy is demonstrating impressive clinical benefit in different malignancies and clinical oncologists are increasingly turning their attention to immune-oncology. It is now well recognized that innate and adaptive immune cells infiltrating tumors are associated with clinical outcomes and responses to treatments, and can be harnessed to patients' benefit. Considerable advances have also been made in understanding how cancers escape from immune attack. Targeting of immunological escape processes regulated by the expression of immune checkpoint receptors and ligands and the down-modulation of tumor antigen presentation is the basis of immuno-oncology treatments. Despite recent achievements, there remain a number of unresolved issues in order to successfully implement cancer immunotherapy in many cancers. Importantly, clinical biomarkers are still needed for better optimization of emerging combination immunotherapies and better treatment tailoring. In this review, we summarize the function of innate and adaptive immune cells in anti-tumor immunity and the general mechanisms exploited by tumor cells to escape and inhibit immune responses as well as therapeutic strategies developed to overcome these mechanisms and discuss emerging biomarkers in immuno-oncology.